2014
DOI: 10.1111/aas.12366
|View full text |Cite
|
Sign up to set email alerts
|

The effects of propofol vs. sevoflurane on post-operative pain and need of opioid

Abstract: In this study, comparing sevoflurane with propofol for maintenance of general anaesthesia, the choice of anaesthetic had no effect on the requirement of oxycodone or intensity of pain after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 25 publications
1
38
1
Order By: Relevance
“…A total of 13 trials reported pain intensity at or around 2 h postsurgery, in which 686 patients received anaesthesia using propofol for maintenance, while 668 were given inhalational anaesthesia [10,11,[18][19][20][21][22][23][24][25][26][27][28]. Overall, pain scores were not significantly different between experimental groups (Hedge's g (95%CI) À0.120 (À0.415-0.175) (p = 0.425) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 13 trials reported pain intensity at or around 2 h postsurgery, in which 686 patients received anaesthesia using propofol for maintenance, while 668 were given inhalational anaesthesia [10,11,[18][19][20][21][22][23][24][25][26][27][28]. Overall, pain scores were not significantly different between experimental groups (Hedge's g (95%CI) À0.120 (À0.415-0.175) (p = 0.425) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A total of nine trials reported pain intensity at or around 24 h postsurgery, in which 595 patients received propofol anaesthesia, while 586 had inhalational anaesthesia [10,11,18,19,21,22,25,28,29]. Overall, compared with inhalational anaesthetics, patients who received propofol reported significantly lower pain scores 24 h postsurgery (Hedge's g (95% CI) À0.134 (À0.248 to À0.021) (p = 0.021) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study comparing isoflurane and propofol for maintenance of general anesthesia, pain scores and postoperative analgesic requirements were comparable in the two groups,45 and in a similar study no difference was found when anesthesia was maintained with sevoflurane versus propofol 46. Finally, a single antiemetic dose of propofol at the end of surgery did not influence pain scores or opioid requirements 47…”
Section: Resultsmentioning
confidence: 89%
“…For example, changes in pain perception are caused in many different ways by anesthetics such as thiopental, which can decrease the pain threshold caused by pressure stimulation and increase heat pain threshold 47. Despite it is the most widely used general anesthetic and exhibits analgesic properties, the clinical use of propofol has been debated 8910. It can decrease pain transmission in the rat spinal cord in vitro and in vivo studies and the subliminal dose of propofol has been reported to increase sensitivity to pain in many cases.…”
Section: Introductionmentioning
confidence: 99%